2017
DOI: 10.1177/0731684417745368
|View full text |Cite
|
Sign up to set email alerts
|

Review of natural fibre-reinforced hybrid composites

Abstract: Natural fibre reinforced hybrid composites which contain one or more types of natural reinforcement are gaining increasing research interest. This paper presents a review of natural fibre reinforced hybrid composites. Both thermoplastic and thermoset composites reinforced by hybrid/synthetic fibres or hybrid/hybrid fibres are reviewed. The properties of natural fibres, the properties and processing of composites are summarised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(80 citation statements)
references
References 116 publications
(377 reference statements)
0
79
0
1
Order By: Relevance
“…Hybrid composites fabrication is done by a combining two or more materials that are reinforced together in a single matrix. A new material structure with more fetching and enhanced properties than their constituent materials and offers an extent of properties that can't be bring off by a single form of reinforcement, whilst reducing their disadvantages [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid composites fabrication is done by a combining two or more materials that are reinforced together in a single matrix. A new material structure with more fetching and enhanced properties than their constituent materials and offers an extent of properties that can't be bring off by a single form of reinforcement, whilst reducing their disadvantages [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, the production of hybrid composites can represent a valid applied compromise. 7,11 Several experimental studies have shown that the hybridization of natural fibers with GFRPs improves tensile, bending, and impact strength of materials. [12][13][14] Furthermore, the positioning of the glass layers at the extremities in the hybrid laminate stacking sequence allows mechanical strength improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Both unidirectional and bidirectional laminates were studied. The typical properties of high strength carbon, E glass, aramid, flax and basalt fibres and epoxy resin are shown in Table 4 [6,8,1,33].…”
Section: Model Applicationmentioning
confidence: 99%